Gender Representation in English Textbooks for Nusantara Kids: A Critical Discourse Analysis Study - Indah Pesona Aisyah; Radinda Rosaria Ramdani; Salma Fathiyah Rahadatul Aisyi; Hapid Ali (Program Studi Pendidikan Bahasa Inggris, ISDIK Kie Raha Maluku Utara, 2026)
This study investigates gender representation in the English textbook